Optimizing sedation in gastroscopy: a study on the etomidate/propofol mixture ratio - Tang, Shuyi; Zheng, Yuling; Li, Xiaoli; Zhang, Yiwen; Zhang, Zhongqi (Frontiers in Medicine, 2024)
Propofol and etomidate are the most commonly used sedative agents in procedural sedation, each with its own advantages and disadvantages. However, there remains considerable controversy regarding the optimal ratio for the mixture of these two drugs, warranting further investigation. Therefore, this study aims to investigate the optimal ratio for combining propofol and etomidate during gastroscopy. Methods: This study is a prospective, double-blinded, randomized controlled clinical trial. One hundred and sixty-two patients from July 2019 to December 2022 were evenly classified into three groups using a random number table as follows: (1) P group (propofol); (2) EP1 group (5ml etomidate + 10ml propofol); (3) EP2 group (10ml etomidate + 10ml), 54 patients per group. The medications, including a pre-sedation dose of 50 µg/kg dezocine followed by sedatives, ceasing when the patient's eyelash reflex vanished, indicating adequate sedation. Mean arterial pressure (MAP), heart rate (HR), and peripheral oxygen saturation (SpO2) measurements taken before anesthesia (T1), immediately after the administration of sedatives (T2), immediately gastroscopic insertion (T3) and immediately recovery (T4) were determined. Additional, perioperative related outcomes and adverse events were also recorded. Results: The EP2 group exhibited a higher MAP at T2 compared to the P and EP1 groups (P < 0.05). Calculated decreases in MAP revealed values of 19.1%, 18.8%, and 13.8% for the P, EP1, and EP2 groups at T2, respectively. Adverse events: Group EP2 exhibited a significantly lower hypotension incidence (11.1%) compared to the Propofol group (50%) and EP1 (31.5%). Concerning injection pain, Group EP2 also showing a significant decrease in comparison to P and EP1 groups (P < 0.05).The use of a mixture of 10 ml etomidate and 10 ml propofol (at a 1:1 ratio) combined with dezocine for painless gastroscopy demonstrates hemodynamic stability, a low incidence of adverse reactions.